Gaya Kepemimpinan dan Motivasiterhadap Kinerja Karyawan pada Bank BJB Cabang Tangerang - Ryani Dhyan Parashakti; Dede Irfan Setiawan (Jurnal Samudra Ekonomi dan Bisnis, 2019)
This study aims to determine the effect of leadership style and motivation on employee performance. The object of this study are employees of Bank bjb Branch Tangerang. This study was conducted on 64 respondents using quantitative descriptive approach. Therefore, the analysis of the data used is the statistical analysis in the form of multiple linear regression.The results of this study addressed that in partial leadership style and motivation have a significant effect on employee performance. This is evidenced from the results of the partial test (t test) to address the significance of the two independent variables that support the hypothesis. Therefore, the test results on this study can be accepted by the statement that the influence of leadership style and motivation have a significant effect on employee performance bjb Bank Branch Tangerang.